Multi Locus Sequence Typing of Multi Drug Resistance Klebsiella Pneumoniae Isolated from different Clinical Samples - J. Jawad. Al – Zubaidi, Saba; R. Rasheed. Al – Taai, Hadi (International Journal of Psychosocial Rehabilitation, 2020)
Klebsiella pneumoniae is an important opportunistic Pathogen, that commonly causes nosocomial infection The problem of antimicrobial resistance is highlighted by a recent increase of antibiotic-resistant A multilocus sequence typing (MLST) scheme was developed for K. pneumoniae. The current study included the collection of two hundred and seventy-eight samples from patients in Baqquba Teaching Hospital in Diyala during the period from December 2018 to May 2019. The samples included urine, sputum, swabs from wounds and burns, and blood. All isolates were diagnosed depending on microscopic and biochemical tests and confirmed by the VITEK2 compact system. It was found (39.4%; n=69) was K. K.pneumoniae and 26% (n=18) of isolates were multidrug-resistant K. pneumoniae. MDR K. pneumoniae showed high resistance against different types of antibiotics; it was as follows: β-lactam groups (AMP 100%, AMC 73.36%, PIP 81.16%, ATM 72.46%, FEP 71.01%, CAZ 62.32%, CRO 56.5%, IPM 27.53%, MEM 26.19%). Aminogly considers groups (AK 47.82%, TOB 43.47%, GM 36.23%). Quinolone groups (LEV 31.82%, OFX 28.98%, CIP 24.63%) and cephalosporin groups (SXT 65.22%). The technique used in this study to determine the genetic diversity of MDR K. pneumoniae was MLST (multilocus sequence typing). Seven housekeeping genes (ropB, gapA, mdh, pgi, phoE, infB, and tonB) were taken from the website of the Institute Pasteur. Eighteen isolates have been used for PCR amplification reaction. Nucleotide variances were seen, and specific alleles for each locus were designated. The allele profile for each isolate was then used to determine sequence type (ST). Seven new isolates, one new isolate, and seven housekeeping genes have been published in NCBI. The MLST approach provides unambiguous data useful for the epidemiology of K. pneumoniae. To the best of our knowledge, this was the first study that involved an MLST analysis of clinical K. pneumoniae isolates from a hospital in Diyala, Iraq.